Study of the scientific work by quantitative methods: some results on Academician Nikola Obreshkoff's works - Todorov, Vassily; Apostolova, Mara; Brankova, Emilia; Zlateva, Stefka; Teneva, Veneta; Khristov, Dimitar (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1997)
Some results of studying the work of one of the most productive Bulgarian mathematician by quantitative methods are presented. The study is based on the data from the world-wide known review journals "Jahrbuch über die Fortschritte der Mathematik", "Zentralblatt für Mathematik und ihre Grenzgebiete" and others, representing most accurate the world scientific information flow, structuring it by domains of science and their areas. Graphically are shown: distribution of Obreshkoff's works over domains of mathematics according to divisions of mentioned review journals, distribution of scientific activity over years, domains of mathematics and their areas, etc. This study is based on the so-called Reference Database (RDB) allowing flexible retrieving, systematizing, aggregation and generalizing data.